Role of 3D Transesophageal Echocardiography for Transcatheter Mitral Valve Repair—A Mini Review - Hirasawa, Kensuke; Izumo, Masaki (Frontiers in Cardiovascular Medicine, 2022)
Edge-to-edge transcatheter mitral valve repair (TMVr) using MitraClip has been evolving rapidly in patients with severe mitral regurgitation (MR) at high surgical risk or having contraindications for surgery. Three-dimensional (3D) echocardiography plays an important role in the management of severe MR. In particular, 3D transesophageal echocardiography (TEE) imaging allows the evaluation of MV geometry and quantification of MR severity with dedicated software. Real-time 3D TEE is also commonly used to guide TMVr and facilitate the procedure. Further development of 3D echocardiography may help achieve safer and more beneficial results. The following article summarizes the current knowledge and the future perspectives of 3D TEE in TMVr.